2017
DOI: 10.1111/puar.12842
|View full text |Cite
|
Sign up to set email alerts
|

The Long Shadow of Police Racial Treatment: Racial Disparity in Criminal Justice Processing

Abstract: This article explores racial disproportionality in criminal justice processing in an era of punitive criminal justice policies and mass incarceration. Using arrest data from New York State, the authors compare the racial disparity in prison sentencing with the disparity at arrest while controlling for crime type and criminal history of the arrest population. Findings show that the racial disparity in prison sentencing at the state level is established before courts begin criminal case proceedings. Scholars and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
(60 reference statements)
3
14
0
Order By: Relevance
“…Though prison sentences occurred at about the same rate, the very large sample sizes result in this difference being statistically significant ( p < 0.001) 4 . This general result is similar to other state‐wide analyses (Beck & Blumstein, 2018; Kim & Kiesel, 2017).…”
Section: County Scorecards On Racial Disparities In Incarcerationsupporting
confidence: 90%
See 2 more Smart Citations
“…Though prison sentences occurred at about the same rate, the very large sample sizes result in this difference being statistically significant ( p < 0.001) 4 . This general result is similar to other state‐wide analyses (Beck & Blumstein, 2018; Kim & Kiesel, 2017).…”
Section: County Scorecards On Racial Disparities In Incarcerationsupporting
confidence: 90%
“…4 This general result is similar to other state-wide analyses (Beck & Blumstein, 2018;Kim & Kiesel, 2017). Examining sentencing disparities only at the statewide level risks missing racial gaps in the incarceration rates in the individual counties.…”
Section: County Scorecards On Racial Disparities In Incarcerationsupporting
confidence: 76%
See 1 more Smart Citation
“…Relatedly, although our data trace people from arrest until case disposition, giving us a broader view into the punishment process, we are still only able to consider racial inequality occurring within the courts post‐arrest. A wealth of recent research has found large racial inequalities in stops, arrests, and other police actions (Beckett et al., 2006; Fagan & Davies, 2000; Geller & Fagan, 2010; Kochel, Wilson, & Mastrofski, 2011; Mitchell & Caudy, 2015), and past research has found racial disparity in arrest patterns explains sentencing inequalities (Kim & Keisel, 2018). We believe our analysis, however, still broadens the conversation around prosecution and sentencing disparities, acknowledging how the criminal justice system is both a product of and a contributor to larger inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in public administration have emphasized the impact of institutions on racial disparities in policing outcomes, as opposed to individual‐level behaviors (Epp, Maynard‐Moody, and Haider‐Markel ; Eterno, Barrow, and Silverman ; Hong ; Jennings and Rubado ; Kim and Kiesel ; Maynard‐Moody and Musheno ; Menifield, Shin, and Strother ; Rivera and Ward ). While these studies effectively demonstrate the relevance and importance of widely prevalent norms, rules, and values in driving racially disparate criminal justice outcomes, the role of accountability institutions has not received sufficient attention.…”
Section: Literature Reviewmentioning
confidence: 99%